Pro Android Games - Silva, Vladimir (Apress : Imprint: Apress, 2009)
Do you remember landmark games like Wolfenstein 3D, Doom, and Asteroids? Well, here's an exciting opportunity to build and/or port these games to one of the hottest mobile and netbooks platforms today: Google's Android. Pro Android Games teaches you how to build cool games like Space Blaster and the classic Asteroids from scratch on the latest Android platform. This book also shows you how to port other classic freeware/shareware games like Doom and Wolfenstein 3D from C using the Java Native Interface (JNI) for Android. This book is all about a unique perspective in Android game development: a well-balanced, powerful combination of pure Java and hybrid game development, mixing Java and C. By combining the elegant object-oriented features of Java and the raw power of C, there is no limit to the types of games that you can build for the platform. With actionable real-world source code in hand, this book allows you to dive right into games development on Android. You'll definitely have fun, and perhaps you'll even make some money. Enjoy!